Analisis Program Evaluation Review Technique (Pert) terhadap Waktu Bongkar Muat Kendaraan - Silvia Dewi Kumalasari; Wiwit prihartono; Danang Darunanto (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
The increasing need for vehicles brings up several problems for loading and unloadingcompanies due to the dominance of cargo vehicles in the car yards, the increasing cargotraffic inside the port every year, the tardiness of export documents from the Shipper / EMKLowners and the increasing intense competition of similar business fields on the same location.By using Evaluation Review Technique Program / PERT , the researchers would like to findout the process of loading and unloadingvehicle , the factors that influence the time forloading and unloading vehicle and the optimal time in scheduling loading and unloadingvehicle. The results show that the time for loading and unloading vehicle is carried out within22:25:00 25 minutes and the critical path at 21:40:00. The factors that influence the length ofloading and unloading vehicle are (a) Delay in providing export documents, (b) Simplesystem for making stowage plan documents, (c) Lack of Human Resources in the process ofloading and unloading vehicles. The optimal time that can be taken is 14:00:00 withopportunities based on a normal table of 0.99988, which means that there is a chance of99.99% of the process loading and unloading vehicles can be completed in the optimal time.